Thio- and Selenocarbonyl Compounds as "Superdienophiles" in [4+2] Cycloadditions - Rohr, Uwe; Schatz, Jürgen; Sauer, Jürgen (European Journal of Organic Chemistry, 1998)
Normal, neutral, and inverse-type Diels-Alder reactions can be observed in [4+2] cycloadditions of thio- and selenocarbonyl compounds 1-9 with various cyclic and aryl-, methyl- or methoxy-substituted open-chain 1,3-butadienes. Extensive kinetic studies prove the highly dienophilic activity of the C=S and C=Se double bond. Studies of the solvent and temperature dependence of the reaction rate indicate a concerted mechanism.